O uso da videomodelação e/ou vídeo prompt no ensino de AVDs para crianças com TEA: uma revisão da literatura - ARAUJO, Elana de Cassia da Silva (2023)
Introduction: Children diagnosed with ASD may have difficulty learning occupations such as ADLs. Videomodeling (VM) is presented as an efficient tool for teaching these occupations, however, there are still cases of failure in its use, which makes it important to carry out a literature review. Objective: Conduct a literature review of publications on the use of VM and VP to teaching activities of daily living for children with ASD. Method: The present study is a literature review, whose inclusion criteria were: 1) experimental, quasi-experimental or single-subject research studies with qualitative results; 2) publications in peer -reviewed journals; 3) one or more participants with ASD; 4) the use of VM and/or prompt performed by professors or researchers in teaching ADLs and/or IADLs; 5) studies published in the electronic databases ERIC and PsycINFO, and the American Journal of Occupational Therapy; in the languages: English, Portuguese and/or Spanish; in the period from September 2012 to February 2022; 6) children, between 0 and 12 years old. Results: Three articles were analyzed, among which efficacy data in two articles and one case of failure regarding the use of VM stand out, as well as considerable differences in the teaching of these skills and their implementation. Conclusion: It is considered that children with ASD can benefit from the use of MV to gain skills to perform ADLs.